Let the numbers be a and b and b>a
2a=3b and 3(b-a)=2(b-a)+13
Solving the first for a:
2a=3b
a=3b/2, now using this value of a in the second equation gives you:
3(b-3b/2)=2(b-3b/2)+13 upon performing indicated operations.
3b-9b/2=2b-6b/2+13 making all terms have a common denominator of 2
(6b-9b)/2=(4b-6b+26)/2 multiplying the whole equation by 2
6b-9b=4b-6b+26 combining like terms
-3b=-2b+26 adding 2b to both sides
-b=26 dividing both sides by -1
b=-26, since a=3b/2
a=3(-26)/2
a=-39
So the numbers are -39 and -26
check...
2a=3b becomes:
2(-39)=3(-26)
-78=-78
3(b-a)=2(b-a)+13 becomes:
3(-26--39)=2(-26--39)+13
3(13)=2(13)+13
39=26+13
39=39
correct :P